2011
DOI: 10.1111/j.1365-2699.2011.02640.x
|View full text |Cite
|
Sign up to set email alerts
|

Tree species compositional change and conservation implications in the white‐water flooded forests of the Brazilian Amazon

Abstract: Aim  The aim of this study was to use compositional changes in tree species along the Amazon River floodplain in Brazil to identify and characterize biogeographic regions that would serve as broad surrogates for conservation planning.Location  The main course of the Amazon River in Brazil, covering a river distance of approximately 2800 km.Methods  Two sampling methods were employed at specific sites: standardized transects and/or individual‐based samples. Seventy‐three samples were collected from 26 sites at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(41 citation statements)
references
References 43 publications
2
39
0
Order By: Relevance
“…When we compared these results with those obtained in várzea forests, Albernaz et al. () found that Fabaceae (20.29%), Annonaceae (6.08%), Sapotaceae (4.80%), Moraceae (4.79%) and Lauraceae (3.32%) were the richest families, representing almost 40% of the species richness. In terra firme of the Central Amazon, Emidio da Silva et al.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…When we compared these results with those obtained in várzea forests, Albernaz et al. () found that Fabaceae (20.29%), Annonaceae (6.08%), Sapotaceae (4.80%), Moraceae (4.79%) and Lauraceae (3.32%) were the richest families, representing almost 40% of the species richness. In terra firme of the Central Amazon, Emidio da Silva et al.…”
Section: Resultsmentioning
confidence: 91%
“…Flooded forests cover more than 800,000 km 2 of the Amazon lowlands during the high‐water season (Melack & Hess, ) but have been sparsely studied compared with “terra firme” forests. This periodic flooding exerts a strong influence on the structure and composition of plant species, which continuously change along the river channel (Albernaz et al., ; Luize, Silva, Wittmann, Assis, & Venticinque, ; Rosales, Petts, & Knab‐Vispo, ; Wittmann, Junk, & Piedade, ). Forests flooded with white or muddy water, such as water from the Solimões River, are referred to as “várzea” (Sioli, ), while those flooded by black and acidic water, such as that of the Negro River, or by clear water, such as that from the Tapajós River, are referred to as “igapó” (Kubitzki, ; Prance, ).…”
Section: Introductionmentioning
confidence: 99%
“…Less than 1% of the Amazon's floodplain estuarine in Brazil is strictly protected (Albernaz et al, 2012) and our study area is designated as an 'extremely high' priority area for conservation initiatives by the Brazilian government (MMA, 2007). Our results emphasize the need to reinforce the protected area network along the main stem Amazon river and the lower reaches of its tributaries to include areas which do not permit any extractive activities that alter the forest physiognomy.…”
Section: Resultsmentioning
confidence: 99%
“…These seasonal floodings have led to the adaptation of A. jauari and other species to ensure survival when partially or totally submersed during those phases (Piedade et al 2006). The distribution of A. jauari and other plants adapted to this habitat varies according to flooding regimes and seasonality, precipitation patterns around the hydrographic basins and due to evolutionary geographical events, defined by the effect of sediment deposition and erosion on changes in river courses (Albernaz et al 2012).…”
Section: Introductionmentioning
confidence: 99%